Comparing mid-term outcomes and patient satisfaction between percutaneous endoscopic lumbar discectomy and microendoscopic discectomy for foraminal and extraforaminal lumbar disc herniations: a retrospective matched cohort study - Liu, Sen; Zhao, Feng; Yin, Chun-Ping; Zhu, Chao-Hua; Zhao, Ruo-Yu; Liu, Guo-Bin; Ji, Gang; Chen, Jia; Gao, Hong-Yang (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to compare the mid-term outcomes and patient satisfaction between percutaneous endoscopic lumbar discectomy (PELD) and microendoscopic discectomy (MED) for the treatment of foraminal and extraforaminal lumbar disc herniations.MethodsA retrospective matched cohort study was conducted, including patients diagnosed with foraminal or extraforaminal lumbar disc herniations who underwent PELD or MED between January 2014 and December 2021. Patient demographics, clinical characteristics, and perioperative data were analyzed. Primary outcomes included Visual Analog Scale (VAS) scores for pain, Japanese Orthopaedic Association (JOA) scores and improvement rates for functional status, and overall satisfaction at a minimum 2-year follow-up.ResultsA total of 133 patients were included in the final analysis. The PELD group demonstrated a significantly greater reduction in VAS scores for low back pain (6.74 ± 1.21 to 1.95 ± 0.42) compared to the MED group (6.93 ± 1.17 to 2.35 ± 0.89) at the 2-year follow-up (p < 0.001). Both groups exhibited significant improvements in JOA scores, with no notable differences observed at the final follow-up. Patient satisfaction rates were higher in the PELD group, with 86% reporting high satisfaction compared to 72% in the MED group; however, this difference was not statistically significant. Logistic regression analysis identified VAS scores for low back pain, operation cost, and symptom recurrence as independent factors influencing patient dissatisfaction at 2 years post-surgery.ConclusionBoth PELD and MED demonstrated efficacy in treating foraminal and extraforaminal lumbar disc herniations over a 2-year follow-up period. PELD, however, exhibited superior relief of low back pain. Factors, such as low back pain intensity, surgical costs, and symptom recurrence significantly impacted patient dissatisfaction, despite comparable overall satisfaction rates between the two surgical techniques.